ASPEK HUKUM TERHADAP SELEKSI PENERIMAAN CPNS TAHUN 2018 - Wahyuni Wahyuni (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Civil servant candidates (CPNS) recruitment is an important series of activities in order to have a Civil Servant with integrity, professionalism, neutral, free from political intervention, free from corrupt, collusion and nepotism (KKN) practices, and is able to provide public services to the community as well as to be a role model to promote national unity based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Therefore, in the selection process the organizers need to carefully prepare everything to minimize the possible legal polemic. Issue related to threshold policies that suddenly change was fully discussed in the last civil servant enrollment test (CPNS) 2018. That change cannot be separated from the discussion of legal aspects when there are some CPNS participants who feel disadvantaged. Basically policy is made to be in line laws and regulations, thus Ministry for the Empowerment of The State Apparaturs Regulation (Permenpan) 37/2018 and Permenpan 61/2018, policies should provide a sense of justice, legal certainty and usefulness.